Elaboración de un plan estratégico de marketing para la matriz de la Cooperativa de Ahorro y Crédito Integración Solidaria Ltda. del cantón Salcedo, provincia de Cotopaxi - Pilamunga Pilamunga, Angel Rafael (2014)
This paper developed the theme entitled "DEVELOPMENT OF A STRATEGIC PLAN FOR THE MATRIX MARKETING COOPERATIVE SAVINGS AND CREDIT LTD PARTNERSHIP INTEGRATION. CANTON SALCEDO” Cotopaxi province ",whose overall objective was to propose a Strategy Marketing Plan for Cooperative matrix then the development of this research work: In summary, a synthesis of the whole structure of the research work described; Introduction on the importance of the research topic in Literature Review, highlights the inherent information to issue specifically in the part of the framework, then the framework is noted the information about their theoretical contexts Strategic marketing plan is summarized with respective references, have after Materials and Methods, the methods outlined here: deductive, inductive, descriptive, analytical and research techniques used as direct observation on the institution and its environment, the interview applied to Mr. manager and surveys applied to cooperative members and employees; It should be noted that implementation of the surveys were conducted to the sample of 366 members and the second survey to 22 employees of the parent of the Cooperative. Later in the Results, was first points out the external analysis, considering, political-legal, social, technological, competitive, economic factors together with the five forces of Porter, being the weighted total of the EFE matrix 2.72, this means that the cooperative has a high degree of opportunity that guarantees continuity and positioning in the local market. The Internal Analysis determined that the weighted total obtained through the EFI matrix is 2.56, so the cooperative has a high degree of strength and a strong internal position which ensures you to move forward and develop positively their environment; in these matrices is considered that the values cannot be greater than 4 or less than 2.5 so that they are in an acceptable range. Earn the opportunities, threats, strengths and weaknesses, High Impact Matrix was performed and then the combination of the analysis; FO, DO, FA, DA, the following strategic objectives are obtained: Diversify and expand the financial services of the Credit Union and Credit "Integration Partnership" Ltda, creating several additional services,. Develop a Plan Promotions and Incentives to members of the Cooperative; Suggest a continuous and permanent employees of the Cooperative training, and develop and implement a plan of Advertising. Also proposed after analysis we can state that the total cost for the implementation of the Strategic Plan are American $ 7,570.00. The most important conclusions of the research are the following: That the Savings and Credit Cooperative "Integration Partnership Ltd., does not have a Strategic Marketing Plan that allows for effective operations in the area of marketing for better positioning in the market ; Although the perception of customers is different, we can say that the interest rates and loan terms are relatively convenient; why the implementation of an incentive plan is necessary, the same as described in detail in the strategic objectives and with respect to the Mission, Vision and Institutional Values, need to be updated periodically in a time of five , so to date is due to propose a different, and how recommendations are highlighted by this research work is delivered to the Cooperative Savings and Credit "Partnership for Integration" Ltda, and they are the ones who implement this Strategic Plan marketing, in order to use as relevant proposals arising from the strategic objectives. The National University of Loja, in a campaign of socialization and support for community development and society in general, publish these works, so the investigative work of the Ecuadorian University becomes apparent. Finally on the part of Bibliography, is given to the sources of information used in the development of research and finally found the Annexes, in which the summary of the draft describes the formats of surveys of customers and workers and the format of the interview Cooperative Savings and Credit "Partnership for Integration.